2022
DOI: 10.37363/bnr.2022.3169
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Burnout Risk among Emergency Nurses during COVID-19 Pandemic

Abstract: Introduction: The Emergency Department (ED) nurses are the first health care professionals to treat patients infected during COVID-19 pandemic. The workload of ED nurses is quite heavy because generally patients who are rushed to the ED are emergency patients who need to get health services as quickly and accurately as possible. This study aimed to determine the prevalence and associated factors of burnout risk among Emergency Nurses during COVID-19 pandemic in Bali. Methods: A cross-sectional study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The results of the current study revealed that; there was no significant statistical relationship between the socio-demographic characteristics of the emergency nurses and the mean scores of CBI (P values > 0.05 for all). This finding goes in the same line with previous studies, which concluded that there was no association between burnout and socio-demographic factors such as age, gender, education level, marital status, and work position ( 15 , 23 ). However, the results revealed that all burnout mean scores in all sub-dimensions of CBI were higher in old ages, males, non-Saudi, divorced, with lower educational levels, nursing technicians, and low years of experience.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of the current study revealed that; there was no significant statistical relationship between the socio-demographic characteristics of the emergency nurses and the mean scores of CBI (P values > 0.05 for all). This finding goes in the same line with previous studies, which concluded that there was no association between burnout and socio-demographic factors such as age, gender, education level, marital status, and work position ( 15 , 23 ). However, the results revealed that all burnout mean scores in all sub-dimensions of CBI were higher in old ages, males, non-Saudi, divorced, with lower educational levels, nursing technicians, and low years of experience.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, another study stated that more than half of the respondents had personal burnout, and more than one-third had work-related and client-related burnout ( 20 ). However, in other study the researcher found that the study subjects had lower burnout means that ranged from 9.8 to 34.58 ( 15 ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Concentrating on how coping mechanisms, both problem-and emotion-focused, were shown to effectively treat psychological distress during the COVID-19 pandemic [12], [13].…”
Section: Mind Mattersmentioning
confidence: 99%
“…has revealed that high demands of workload had led to the excessive physical and mental work, resulting in nurses' fatigue [4]- [6]. In addition, the large number of complaints and demands from the patient's family also increase the nurses' workload [7], as well as impacted the nurses fatigue.…”
Section: Introductionmentioning
confidence: 99%